2018
DOI: 10.4401/ag-7655
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic and volcano-tectonic activity forecasting: a review on seismic approaches

Abstract: Forecasting volcanic activity is a difficult problem that is being addressed worldwide from different perspectives. Significant advances have been made after the introduction of non-linear dynamical systems theory and the use of power-law distributions of different geophysical parameters in the Earth Sciences. In particular, frequency-magnitude power-law statistics evidences the scale-invariance and self-organization of seismicity, and brittle fracture models show that under certain conditions, a precursory ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Several data reduction methods [27] have been proposed to characterize its short-and long-term time evolution, that can lead to the identification of significant transitions between volcanic processes [28], sometimes triggered by external or internal events such as tectonic or volcano-tectonic (VT) seismic events [29]. Volcanic tremor can also occur precursory to an eruption [30][31][32][33]. However, the origins of tremor may vary at different volcanoes, and are often poorly understood; moreover, many different seismic sources can act at the same time and combine to produce the signal of interest [27].…”
Section: Introductionmentioning
confidence: 99%
“…Several data reduction methods [27] have been proposed to characterize its short-and long-term time evolution, that can lead to the identification of significant transitions between volcanic processes [28], sometimes triggered by external or internal events such as tectonic or volcano-tectonic (VT) seismic events [29]. Volcanic tremor can also occur precursory to an eruption [30][31][32][33]. However, the origins of tremor may vary at different volcanoes, and are often poorly understood; moreover, many different seismic sources can act at the same time and combine to produce the signal of interest [27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have shown that the duration of swarms that result in volcanic activity can vary significantly (McNutt, 2005), making eruption forecasting difficult. Moreover, in many cases, a sudden increase in earthquake activity, even for highly active volcanoes, has not resulted in a volcanic eruption (Ramis et al, 2018;Gudmundsson, 2020). To enhance the precision and consistency of earthquake swarms in volcanic eruption forecasts, it would be advantageous to develop a more objective and statistically-driven methodology for identifying various types of earthquake sequences.…”
Section: Introductionmentioning
confidence: 99%